Efektivitas Layanan Sahabat Perempuan dan Anak (SAPA) 129 (Studi Kasus Kualitas SDM Pada Layanan SAPA 129 di Kementerian PPPA) - Anggin Nuzula Rahma; Pracoyo Cipto Nugroho; Retno Damayanti; Tri Mulatasih (Jurnal Good Governance, 2022)
The Ministry of Women's Empowerment and Child Protection has launched the Call Center Service Friends of Women and Children (SAPA) 129 in collaboration with PT Telekomunikasi Indonesia (PT Telkom Indonesia) on March 8, 2021. The SAPA 129 service is one form of implementation of Presidential Regulation Number 65 of 2020 related to the addition of the duties and functions of the Kemen PPPA as a final referral service provider for women victims of violence. The SAPA 129 service is a revitalization of the public complaint service as a tangible manifestation of the state's presence in protecting women and children. SAPA 129 services are carried out by the Deputy for Protection of Women's Rights and the Deputy for Special Protection for Children. Based on data from the PPPA Ministry, the number of reports of cases of violence against women and children from March 2021 to February 2022 increased sharply. However, this increase in the number of reports did not increase with the increase in the number and quality of Human Resources (HR) owned by the Ministry of PPPA. This study aims to determine the effectiveness of SAPA 129 services related to handling cases of violence against women and children. The research method used is a qualitative approach, with primary data sources in the form of interviews, observations, and data triangulation. An alternative solution that can be provided is by conducting training or technical guidance related to the 6 functions of SAPA 129 services. The strategy adopted is networking with cross-Ministerial / Institutional and Community Institutions, especially those that have service institutions for handling cases and children in the implementation of training and technical guidance as well as sharing knowledge / good practice in optimizing SAPA services 129.Keywords: Public Service; Violence; Women; Children